Answer:
- -2/a³ m/s
- -2 m/s
- -1/4 m/s
- -2/27 m/s
Step-by-step explanation:
The velocity is the derivative of position:
v = ds/dt = (d/dt)(t^-2) = -2t^-3
For t=a, the velocity is
-2a^-3 = -2/a³ . . . . meters per second
For t=1, the velocity is ...
-2·1³ = -2 . . . . meters per second
For t=2, the velocity is ...
-2·2^-3 = -2/8 = -1/4 . . . . meters per second
For t=3, the velocity is ...
-2·3^-3 = -2/27 . . . . meters per second
Answer:
no solution
Step-by-step explanation:
__________
The last option because he spent $135 or more
<span>The answers to this problem are:<span>(<span>±5</span></span>√3/8,±5/8)<span>Here is the solution:
Step 1: <span><span><span>x2</span>+<span>y2</span>=<span>2516</span>[2]</span><span><span>x2</span>+<span>y2</span>=<span>2516</span>[2]</span></span>
Step 2: Substitute:<span>
</span><span><span>8<span><span>(<span>25/16</span>)^</span>2</span>=25(<span>x^2</span>−<span>y^2</span>)
</span><span>8<span><span>(<span>25/16</span>)^</span>2</span>=25(<span>x^2</span>−<span>y^2</span>)</span></span>
</span><span>x^2</span>−<span>y^2</span>=<span>25/32</span><span>.
Add [2] and [3]:<span>
</span><span>2<span>x^2</span>=<span>75/32
</span><span>x^2</span>=<span>75/74</span></span>
<span>x=±5</span></span>√3/8<span>
Substitute into [2]:<span>
</span><span><span>75/64</span>+<span>y^2</span>=<span>50/32
</span><span>y^2</span>=<span>25/64</span></span>
<span>y=±<span>5/8</span></span>
</span>
</span>